1990
DOI: 10.1128/jvi.64.12.6263-6269.1990
|View full text |Cite
|
Sign up to set email alerts
|

Activity of rat Mx proteins against a rhabdovirus

Abstract: Upon stimulation with alpha/beta interferon, rat cells synthesize three Mx proteins. Sequence analysis of corresponding cDNAs reveals that these three proteins are derived from three distinct genes. One of the rat cDNAs is termed Mxl because it is most closely related to the mouse Mxl cDNA and because it codes for a nuclear protein that, like the mouse Mxl protein, inhibits influenza virus growth. However, this protein differs from mouse Mxl protein, in that it also inhibits vesicular stomatitis virus (VSV), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(82 citation statements)
references
References 25 publications
4
77
0
1
Order By: Relevance
“…The rat Mx2 and Mx3 genes are 98% similar and the respective proteins differ by only eight amino acids [Lee and Vidal, 2002]. Using plasmids containing rat Mx1, Mx2, or Mx3 [Meier et al, 1990], PCR primers were designed that were specific for each Mx gene and that did not cross-react with the other Mx genes. Quantitative RT-PCR data revealed that Mx2, and to a lesser extent Mx1, was downregulated in male rats 15 days after infection (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The rat Mx2 and Mx3 genes are 98% similar and the respective proteins differ by only eight amino acids [Lee and Vidal, 2002]. Using plasmids containing rat Mx1, Mx2, or Mx3 [Meier et al, 1990], PCR primers were designed that were specific for each Mx gene and that did not cross-react with the other Mx genes. Quantitative RT-PCR data revealed that Mx2, and to a lesser extent Mx1, was downregulated in male rats 15 days after infection (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Murine Mxl synthesized in insect cells via a baculovirus expression system was purified to homogeneity (47) and found to aggregate into dimers and trimers. The aggregating properties of Mx had previonsly been suggested by immunofluorescence studies on the cytoplasmie human Mx proteins and the nuclear mouse and rat Mx proteins, all of which stain as distinctly punctate aggregates (61)(62)(63)(64)(65)4). Large Mxl aggregates were observed in the nuclei of interferon-treated A2G cells under immunoelectroii-microscopic examination.…”
Section: Protein Structurementioning
confidence: 96%
“…Rat Mxl is localized in the nucleus and shares 79% amino acid identity with the nuclear murine Mxl. Rat Mx2 and Mx3 are cytoplasmie proteins and differ from each other by only eight amino acids (7). When 3T3 cells were microinjected with expression plasmids for rat Mxl, Mx2, or Mx3 and challenged with influenza virus or VSV, the rat Mxl strongly inhibited influenza virus production and to a lesser degree inhibited VSV production.…”
Section: Antiviral Activity Of Cloned MX Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of ISGs including Mx1, PKR, IFITM3, and tetherin have previously been reported to inhibit VSV replication (21)(22)(23)(24). However, it was not known whether this list represents a complete catalogue of ISGs proteins with anti-VSV activity.…”
Section: Discussionmentioning
confidence: 99%